Pulmonary vascular adaptations to hypoxia in elite breath-hold divers - Kjeld, Thomas; Isbrand, Anders Brenøe; Arendrup, Henrik Christian; Højberg, Jens; Bejder, Jacob; Krag, Thomas O.; Vissing, John; Tolbod, Lars Poulsen; Harms, Johannes Hendrik; Gormsen, Lars Christian; Fuglø, Dan; Hansen, Egon Godthaab (Frontiers in Physiology, 2024)
Introduction: Elite breath hold divers (BHD) possess several oxygen conserving adaptations to endure long dives similar to diving mammals like the Dolphin. During dives, Bottlenose Dolphins may increase the alveolar ventilation (VA) to perfusion (Q) ratio to increase alveolar oxygen delivery. We hypothesized that BHD possess similar adaptive mechanisms during apnea. Methods and results: Pulmonary blood volume (PBV) was determined by echocardiography, 15O-H2O-PET/CT, and cardiac MRi, whereas the oxygen binding properties of the hemoglobin was quantified by arterial blood gas analyses before, during and after maximum pool apneas. Pulmonary function was determined by body box spirometry and compared to matched controls. After 2 min of apnea, PBV determined by echocardiography and 15O-H2O-PET/CT decreased 26% and 41%, respectively. After 4 min of apnea, PBV assessed by echocardiography and cardiac MRi decreased further by 48% and 67%, respectively (n=6). Fractional saturation (F)O2Hb determined by arterial blood-gas-analyses collected after warm-up and a 5-minute pool-apnea (n=9) decreased 43%. Compared to matched controls (n=8), spirometry revealed a higher total and alveolar-lung-capacity in BHD (n=9), but a lower diffusion-constant. Conclusion: Our results contrast with previous studies, that demonstrated similar lung gas transfer in BHD and matched controls. We conclude that elite BHD 1) have a lower diffusion-constant than matched controls, and 2) gradually decreases PBV during apnea and in turn increases VA/Q to increase alveolar oxygen delivery during maximum apnea. We suggest that BHD possess pulmonary adaptations similar to diving mammals to tolerate decreasing tissue-oxygenation.